The evident and the hidden factors of vitamin D status in older people during COVID-19 pandemic - Schmidt Azevedo, Paula [UNESP]; Fock, Ricardo Ambrosio; Pereira, Filipe Leal [UNESP]; dos Santos, Priscila Portugal [UNESP]; Ferro, Flavio Cruz [UNESP]; Sacco, Nataly [UNESP]; Polegato, Bertha Furlan [UNESP]; Zornoff, Leonardo Mamede [UNESP]; Okoshi, Marina Politi [UNESP]; Achterberg, Wilco; de Paiva, Sergio Rupp [UNESP] (Springer Nature, 2021)
Purpose: Considering the COVID-19 pandemic, vitamin D is a target of research and speculation. Lockdown or home isolation reduces sunlight exposition and increases the risk of vitamin D deficiency. Special attention is needed for older people at risk of both severe forms of COVID-19 and vitamin D deficiency. This review aims to highlight the association of vitamin D and COVID-19 in two instances, the direct influence of vitamin D on the immune system, and the indirect risks for other vitamin D deficiency-related diseases, such as musculoskeletal properties in older persons. Methods: We performed a narrative review. Results: Whether vitamin D deficiency is associated with COVID-19 poor prognosis, and if vitamin D supplementation may improve the post-infection outcomes is still unclear. In any case, the pandemic generates indirect burden, such as the sequence: home isolation, low sunlight exposition, vitamin D deficiency, and fragility fractures. Conclusion: Therefore, it is time to debate how to optimize vitamin D status in older people, especially during the COVID-19 pandemic.
Keywords: Care homes; COVID-19; Frailty; Older people; Vitamin D